Estimating the recreational value of Taal Volcano Protected landscape, Philippines using benefit transfer - Vista, Arvin B. (Journal of Environmental Science and Management, 2015)
When protected landscapes serve as popular recreational resources and destinations, then they may hold significant use values for those people that visit them. Recognition of these recreational benefits of protected landscapes provides a sound economic rationale for their management. This study provides estimates of the recreational value via benefit transfer of Taal Volcano Protected Landscape in the Philippines. One study site in the Philippines was selected and used in a point estimate transfer application. Likewise, a metaregression transfer function model was estimated based on selected ‘study sites’ from the US. Results show that point estimate transfer approach provided a conservative estimate of the recreational value of the site than the international meta-regression benefit function transfer approach. The estimated average welfare estimate of recreational access using point estimate transfer was PhP 26 per person per trip in 2011 and PhP 1,696 per person per trip in 2011 using the meta-regression benefit transfer function.